Kepemimpinan Kepala Sekolah Dalam Pengawasan Kinerja Guru Dan Proses Pembelajaran - Yuswanto, Anang; Zamroni, Afif; Asy’ari, Hasyim (Chalim Journal of Teaching and Learning, 2022)
Data collection techniques used in this study include structured interviews, observation and documentation with the data subject of the MI Madrasah principal Alhikmah Ngareskidul Gedeg Mojokerto. Data analysis was carried out during data collection, and after collection within a certain period. As a test of the validity of the data, a credibility test is used or a trust test for the data presented by the research results. The results of the study indicate that supervision has been carried out in teacher performance and the learning process at MI Alhikmah Ngareskidul Gedeg Mojokerto supervision of attendance discipline, learning planning discipline, learning implementation discipline, and learning outcomes assessment discipline. In addition, the principal has also carried out supervision in the completeness of teacher administration and the ability of teachers to master the use of information technology. Supervision of the learning process includes monitoring the planning, implementation and assessment of learning. As a suggestion, school principals are expected to play a more active role in Madrasah Working Groups (KKM) and motivate teachers to be more active in participating in KKG (Teacher Working Group) activities.